From Waste to Value: Mapping Global Research Trends in Product Engineering and Circular Economy in Agro-Industry - Muhamad Dupi; Ipan Saputra (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2026)
The paper examines the trends in research on product engineering and the management of agro industry waste on the basis of bibliometric analysis with the help of Scopus and VOSviewer (version 1.6.20). The study analyzed 1,157 articles published between 2000 and 2025, networks of collaboration, leading journals, leading authors and institutions, as well as new research directions. As depicted by the results of the analysis, after 2017, publications have seen a considerable growth up to 2024, caused by the implementation of the principles of the circular economy and technological advancement as well as attempts to use waste as a resource. Network visualization of collaboration showed three prominent groups of international cooperation in terms of integration of developed and developing nations, whereas keyword analysis ranked the term circular economy as the core junction relating to sustainability, biorefinery, and life cycle assessment topics. Nevertheless, there are some issues that are yet to be addressed, among them being heterogeneity of waste, technological gaps in developing nations and low market penetration of products made using waste. The results highlight the need to integrate technological innovation, international cooperation, and circular economy principles for sustainable agro industry waste management and future research and policy development.